Biomedical applications of nanodiamonds in imaging and therapy. (December 2013) - Perevedentseva, Elena; Lin, Yu-Chung; Jani, Mona; Cheng, Chia-Liang
Nanodiamonds have attracted remarkable scientific attention for bioimaging and therapeutic applications owing to their low toxicity with many cell lines, convenient surface properties and stable fluorescence without photobleaching. Newer techniques are being applied to enhance fluorescence. Interest is also growing in exploring the possibilities for modifying the nanodiamond surface and functionalities by attaching various biomolecules of interest for interaction with the targets. The potential of Raman spectroscopy and fluorescence properties of nanodiamonds has been explored for bioimaging and drug delivery tracing. The interest in nanodiamonds' biological/medical application appears to be continuing with enhanced focus. In this review an attempt is made to capture the scope, spirit and recent developments in the field of nanodiamonds for biomedical applications.